Molecular characterization of enolase gene from Taenia multiceps. (October 2015) - Li, W.H.; Qu, Z.G.; Zhang, N.Z.; Yue, L.; Jia, W.Z.; Luo, J.X.; Yin, H.; Fu, B.Q.
Abstract: Taenia multiceps is a cestode parasite with its larval stage, known as Coenurus cerebralis, mainly encysts in the central nervous system of sheep and other livestocks. Enolase is a key glycolytic enzyme and represents multifunction in most organisms. In the present study, a 1617 bp full-length cDNA encoding enolase was cloned from T. multiceps and designated as TmENO. A putative encoded protein of 433 amino acid residues that exhibited high similarity to helminth parasites. The recombinant TmENO protein (rTmENO) showed the catalytic and plasminogen-binding characteristics after the TmENO was subcloned and expressed in the pET30a(+) vector. The TmENO gene was transcribed during the adult and larval stages and was also identified in both cyst fluid and as a component of the adult worms and the metacestode by western blot analysis. Taken together, our results will facilitate further structural characterization for TmENO and new potential control strategies for T. multiceps . Highlights: A full-length cDNA encoding enolase from T. multiceps was cloned. The TmENO gene was transcribed at the adult and metacestode in the T. multiceps life cycle. Enolase genes were highly conserved among the helminths. rTmENO fusion proteins showed the ability of catalytic and plasminogen-binding.